South Col : One Man's Adventure on the Ascent of Everest, 1953 - Noyce, Wilfrid; Foreword By Hunt, John Sir (William Heinemann Ltd. Melbourne, 1954)
Wilfrid Noyce was the first member of the 1953 Everest expedition to accomplish the ascent of the South Col, the small plateau just below the summit. His memoir captures the numbing feeling of intense cold, the shriek of high winds, and the austere beauty of glacier and snowfall and stone.
Include Index and Illustration
Keywords: Noyce, Wilfrid, 1917-1962 -- Asia--Mount Everest -- Mountaineers